The Restoration of Welfare Economics - Atkinson, Anthony B (American Economic Review, 2011)
This paper argues that welfare economics should be restored to a prominent place on the agenda of economists, and should occupy a central role in the teaching of economics. Economists should provide justification for the ethical criteria underlying welfare statements, and these criteria require constant re-evaluation in the light of developments in economic analysis and in moral philosophy. Economists need to be more explicit about the relation between welfare criteria and the objectives of governments, policy-makers and individual citizens. Moreover, such a restoration of welfare economics should be accompanied by consideration of the adoption of an ethical code for the economics profession.